Analysis on physical and mechanical performance and damage mechanism of steel strand under coupling effects of load and environment. Issue 11 (18th July 2018) - Meng, Ercong; Yao, Guowen; Yu, Yalin; Jiang, Dongxia
Abstract : To study the physical and mechanical performance and damage mechanism of steel strand under coupling effects of load and environment, with the changing parameters of different corrosion time and load forms, 16 groups with totally 32 specimens were designed under coupling effects of load and environment. The test results show that the corrosion weight loss rate P w presents the increasing trend with the increase of corrosion time, but the increasing rate gradually decreases, and the P w increasing trend accords with the Boxlucass function model. The tensile strength of specimens presents the decreasing trend with the increase of corrosion time in the stage of etch pits nucleating and expanding, but the decreasing trend is relatively small, within 5%. The P w of specimens under alternate load working condition is the biggest; under static load condition follows and under no load condition is the lowest. Different load forms have little effect on the tensile strength. Based on Boxlucass function model, the relationship between P w and corrosion time under different load forms were fitted out, respectively. The research results can provide reference for some related research. Abstract : This paper aims to study the physical and mechanical performance and damage mechanism of steel strand under coupling effects of load and environment with the changing parameters of different corrosion time and load forms. Based on experimental data, it was found that the corrosion weight loss rate of specimens under alternate load working condition is the biggest; under static load condition follows and under no load condition is the lowest.